Managing 'human resources' by exploiting and exploring people's potentials - Holmqvist, Mikael, 1970-; Spicer, André (Research in the sociology of organizations ;, 2013)
Organizations are under constant pressure to be ambidextrous. They must be able to exploit existing processes, routines and systems at the same time as they must engage in exploration through playfulness, relaxed control and experimentation. We know little about the human costs and challenges of ambidexterity. In this volume we explore the impact of ambidextrous organizations on individuals' working lives. The authors analyze how employees are required to follow routines at the same time as they are expected to break these routines. They also explore how the individual dilemmas of ambidexterity play out in the lives of precarious work, online communities, management consultants, workers in the automotive industry, and consumers of pop-management books in the US. The result is a rich and fascinating picture of individuals whose working lives are made up of a continued tension between the quest to be exploitative and explorative.